Introduction of article-processing charges for Population Health Metrics - Murray Christopher JL; Mathers Colin D (BMC, 2003)
Abstract Population Health Metrics is an open-access online electronic journal published by BioMed Central - it is universally and freely available online to everyone, its authors retain copyright, and it is archived in at least one internationally recognised free repository. To fund this, from November 1 2003, authors of articles accepted for publication will be asked to pay an article-processing charge of US$500. This editorial outlines the reasons for the introduction of article-processing charges and the way in which this policy will work. Waiver requests will be considered on a case-by-case basis, by the Editor-in-Chief. Article-processing charges will not apply to authors whose institutions are 'members' of BioMed Central. Current members include NHS England, the World Health Organization, the US National Institutes of Health, Harvard, Princeton and Yale universities, and all UK universities. No charge is made for articles that are rejected after peer review. Many funding agencies have also realized the importance of open access publishing and have specified that their grants may be used directly to pay APCs.